Greening the justice system: assessing the legality, feasibility, and potential of artificial intelligence in advancing environmental sustainability within the Indian judiciary - G, Anbarasi; D, Sankar (Frontiers in Political Science, 2025)
This study examines the integration of Artificial Intelligence (AI) in the Indian judiciary system, focusing on its potential to address environmental sustainability and climate change challenges while improving judicial efficiency. The Indian courts’ traditional paper-based operations contribute significantly to environmental degradation, necessitating technological solutions for a greener justice system. The research analyzes the current state of AI implementation in Indian courts through examination of three major initiatives: SUPACE (Supreme Court Portal for Assistance in Court Efficiency), SUVAS (Supreme Court Vidhik Anuvaad Software), and various e-Court projects. The study evaluates both environmental impact data and technological implementation reports from the Supreme Court’s E-Committee and Ministry of Law and Justice. The implementation of AI-driven systems has shown promising results, with SUVAS successfully translating over 36,271 Supreme Court judgments into Hindi and 17,142 judgments into 16 regional languages by 2024. Virtual hearings between 2020 and 2023 prevented an estimated 50,000 metric tons of carbon emissions through reduced travel. While AI integration shows significant promise in reducing environmental impact and improving judicial efficiency, the study identifies key challenges including the need for comprehensive legislation governing AI use in judiciary, substantial infrastructure requirements, and data privacy concerns. The recent allocation of ₹1,500 crore for Phase III of the e-Courts Project and the implementation of the Digital Personal Data Protection Act demonstrate strong governmental commitment to technological advancement in judiciary while addressing legal and privacy concerns.